Documenting and analyzing the Kaledupa flora and fauna lexicon: A mixed-methods study on language shift and marine conservation - La Djamudi Nadir; Hamka Nurhadi; Adam Sutisno; Suherman La Ode Achmad; Riniati Wa Ode; Nazar Asrul (BIO Web of Conferences)
Language and biodiversity are disappearing at alarming rates, often due to interconnected factors. This study investigates the flora and fauna lexicon of the Kaledupa language—spoken on Kaledupa Island, Southeast Sulawesi—as a case of how linguistic and ecological knowledge co-evolve and decline together. The research aims to classify the morphological structure of the lexicon, assess its vitality across social demographics, and identify contributing factors to its erosion. Using a mixed-methods approach, the study combines ethnolinguistic documentation with a quantitative survey of 120 local residents differentiated by age, education, and occupation. Qualitative findings reveal 41 lexemes—categorized into singular, reduplicative, and compound forms—each tied to cultural and ecological meanings. Quantitative data show a marked decline in lexical knowledge among younger, formally educated individuals, with reduced marine interaction correlating to decreased usage. Lexicons linked to endangered species were the least recognized. A statistically significant correlation between age, occupation, and lexicon retention suggests that traditional ecological knowledge is closely bound to generational practice. The study contributes to linguistics, ecolinguistics, and conservation by emphasizing the role of language in sustaining biodiversity. It recommends integrating local lexicons into conservation and education programs to preserve both environmental and cultural heritage.